Age, oxidative stress exposure and fitness in a long‐lived seabird. (28th October 2015) - Herborn, Katherine A.; Daunt, Francis; Heidinger, Britt J.; Granroth‐Wilding, Hanna M. V.; Burthe, Sarah J.; Newell, Mark A.; Monaghan, Pat
Summary: The need to manage exposure to oxidative stress, which can damage macromolecules, is thought to influence the resolution of life‐history trade‐offs. Oxidative damage is expected to increase with age as a consequence of changes in the optimal investment in defences or repair, and/or because of senescence in antioxidant defence systems, although the pattern might differ between short and long‐lived species. However, data on age‐related changes in damage levels in wild populations are rare. Using cross‐sectional and longitudinal data collected over 3 years, we examine variation in a measure of oxidative damage exposure in known age, wild European Shags ( Phalacrocorax aristotelis ), a relatively long lived species. The cross‐sectional data showed a quadratic relationship between oxidative damage exposure and age: both relatively young and old adults had higher levels than those in middle age. In contrast, a measure of non‐enzymatic antioxidant levels did not vary with age. The cross‐sectional increase in oxidative damage exposure in later life was consistent with longitudinal patterns observed within older birds (more than 10 years old). However, the apparent decline in oxidative damage in early adulthood was not consistent with longitudinal patterns in younger birds, which showed individual variation but no consistent age‐related change in the marker. This suggests that cross‐sectional patterns reflect instead higher disappearance of individuals with high exposure to oxidative damage at this life stage. Our data further show that oxidative damage levels are predictive of attendance at the colony in all age classes: juveniles fledging with a high damage exposure index were less likely to be resighted in the breeding colony 2 years later, and adults with high levels at the end of the breeding season had reduced return rates, irrespective of age. Since this is a species that shows high colony fidelity, this is likely to reflect mortality patterns. These data suggest that exposure to oxidative damage increases with age in a long lived species, but only in later life, when high investment in reproduction at the cost of defence would be predicted. Abstract : Lay Summary